Розробка системи моніторингу психофізіологічних параметрів спортсменів для досягнення поліпшення якості стрільби - Рогач, О. О.; Майборода, В. О. (ХНУРЕ, 2020)
The ski race is characterized by a long cycle of dynamic work. Shooting requires a static effort from the athlete, high voltage of mental and physiological functions (rest and concentration, fine coordination of spatial, temporal and power parameters) at the moment of aiming and firing. The combination of these different types of activities makes them interdependent.
Keywords: психофізіологічні параметри; спортсмен